2018
DOI: 10.1038/s41419-018-0721-8
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor Zfp90 regulates the self-renewal and differentiation of hematopoietic stem cells

Abstract: Hematopoietic stem cells (HSCs) can give rise to all blood cells that are essential to defend against pathogen invasion. The defective capability of HSC self-renewal is linked to many serious diseases, such as anemia. However, the potential mechanism regulating HSC self-renewal has not been thoroughly elucidated to date. In this study, we showed that Zfp90 was highly expressed in HSCs. Zfp90 deficiency in the hematopoietic system caused impaired HSPC pools and led to HSC dysfunction. We showed that Zfp90 delet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…We found that the hiPSCs successfully differentiated into HPCs (Figure 9B), and the group treated with 3,2′-DHF showed significantly increased populations of CD34+ CD45+ cells (Figure 9C). Cell identity of HPCs can be defined by gene regulation networks governed by transcription [59] and several previous studies have shown that various transcription factors regulate HPC differentiation and engraftment [60][61][62]. We investigated whether 3,2′-DHF regulates transcription factors after hiPSC differentiation into HPCs and confirmed that the expression of RUNX1, GATA2, ERG, HOXA9, and CXCR4 were increased in the 3,2′-DHF-treated cells (Figure 9D).…”
supporting
confidence: 54%
“…We found that the hiPSCs successfully differentiated into HPCs (Figure 9B), and the group treated with 3,2′-DHF showed significantly increased populations of CD34+ CD45+ cells (Figure 9C). Cell identity of HPCs can be defined by gene regulation networks governed by transcription [59] and several previous studies have shown that various transcription factors regulate HPC differentiation and engraftment [60][61][62]. We investigated whether 3,2′-DHF regulates transcription factors after hiPSC differentiation into HPCs and confirmed that the expression of RUNX1, GATA2, ERG, HOXA9, and CXCR4 were increased in the 3,2′-DHF-treated cells (Figure 9D).…”
supporting
confidence: 54%
“…Hematopoietic stem cells (HSCs), which take on the potency to self-renew and differentiate to all lineage blood cells, play an essential role in hematopoiesis ( 39 , 40 ). Studies have shown that ZFP90 can be used as a transcription factor to participate in the regulation of HSC self-renewal and repopulation potential in vivo ( 41 ). Besides, excessive activation of the Wnt/β-catenin signaling pathway, an important signal pathway to participate in SLE ( 42 ), facilitates HSCs to lose the abilities of differentiation ( 43 , 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Smarca1 participates in the NURF chromatin remodeling complex, that can limit or promote chromatin accessibility, and thus block or activate gene expression correspondingly 43 . NURF complex has been shown to promote cell proliferation, but a role for this complex in RA is missing 63,64 . Recently, a study reported a role for miR-222 in targeting Brg1, a SWI/SNF chromatin remodeling component, leading to repression of inflammatory cytokine expression in sepsis 28 .…”
Section: Discussionmentioning
confidence: 99%